Analysis on Thermal Conductivity Enhancement for PCM Embedded in Metal Foam - 张涛; 余建祖 (Zhileng xuebao)
Analysis for estimating effective thermal conductivity of the phase change thermal energy storage filled up with metal foams was performed. Based on the analysis of metal foam structure, a model consisting of a two-dimensional array of hexagonal cells was established in which the fibers form the sides of the hexagons and the unit cell was assumed as nine heat transfer layers. The functional relations between the effective thermal conductivity and the porosity were derived with the thermal resistance analysis. In addition, numerical data of the effective thermal conductivity with paraffin embedded in aluminum foam and copper foam were compared with those with paraffin embedded in aluminum fin and copper fin. The results indicate that the thermal conductivity and efficiency of the phase change thermal energy storage by filling metal foams are obviously higher than those by filling metal fins.